A poetry precise and free : selected madrigals of Guarini - Guarini, Battista, 1538-1612 (University of Michigan Press, 2018)
A Poetry Precise and Free collects 150 lyric poems by the Renaissance Italian poet Giovanni Battista Guarini in new translations, accompanied by the Italian originals and commentary that will enlighten and engage both scholars and general readers. Guarini's madrigals provide insight into northern Italian court culture of the late Renaissance, when poetry and music were enjoyed as companion arts. Hundreds of composers of Guarini's day set his lyric poems to music. Primarily known today in their vocal settings, most famously those of Claudio Monteverdi, the poems merit appreciation in their own right. This volume is organized into ten sections, grouping the madrigals around themes such as the anguish of passion, the asymmetry of desire, the incursions of jealousy, and the possibility of mutual bliss. Nicholas R. Jones renders Guarini's poetry into accessible contemporary English verse that nevertheless stays true to the substance and form of the original texts, reflecting their roots in the Petrarchan poetic tradition and displaying the emotion and musicality that made these lyrics so popular from the start. A substantive introduction provides cultural context for the madrigals and their musical settings; brief commentaries follow each translation to illuminate aspects of poetic and rhetorical craft. An extensive appendix lists the madrigal compositions that set these lyrics for vocal performance. The book fills a major gap in the scholarship on Guarini's literary legacy. It will appeal to scholars of literature, Renaissance studies, and musicology, early-music performers, and general readers interested in poetry and classical music. Nicholas R. Jones is Professor Emeritus of English, Oberlin College. Also an amateur musician, Jones engages in historically informed performance practice with early music ensembles in the San Francisco Bay Area.